Research on DoS detection and reaction of SIP application - ZENG Shui-fei1; HE Guang-yu2; WEN Ying-you2; WANG Ren-bo1 (Tongxin xuebao)
To resolve the SIP DoS hidden trouble in the ALL-IP fusion network,a novel detection and reaction method was proposed.First,the characteristic of SIP DoS behavior was analyzed deeply to enhance the pertinency of detection.Afterwards,the method used the improved SIP transaction-finite automation（IST-FA） to detect the DoS attacks.Finally,the method took the reaction based on the puzzle challenge mechanism.Simulation and analysis show that the efficiency and performance of the method can satisfy the requirement of SIP DoS prevention.